Ekspolarasi Konsep Fungsi Matematika Dalam Pembuatan Kain Tenun Tradisional Wajo - Ja'faruddin, Ja'faruddin; Khaerati, Khaerati; Aris, Fauzan Abdillah; Jelita, Jelita; Nurdin, Nurazizah; Qalzum, Umrah Nur; Azzahra, Aulia; Ardiyanti, Fifi (Universitas Cokroaminoto Palopo, 2025)
Traditional arts and mathematics share a profound yet often overlooked connection, particularly in the process of traditional textile making. In South Sulawesi, Wajo woven fabric represents a cultural heritage whose production process involves complex mathematical calculations. This research aims to explore and analyze the application of mathematical function concepts in the Wajo weaving process. Data collection was conducted through direct observation of the weaving process, interviews with craftsmen, and documentation studies, which were then analyzed using qualitative descriptive methods. The findings reveal that the Wajo weaving process has a strong correlation with mathematical function concepts, where variables such as thread count, card patterns, and weaving techniques form mathematical relations that generate specific motifs. Understanding this relationship can contribute to the preservation and development of traditional weaving arts through scientific approaches.